Penggunaan Lahan Tidur di Desa Lamorende Kecamatan Tongkuno - Muh. Asrun; Akhmad Marhadi; Zainal Zainal (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
This study aims to determine the use of idle land by the Lamorende Village, Tongkuno District, Muna Regency community. Using James S. Coleman's Rational Choice theory, this research answers the problem of idle land use. The method used is ethnography with in-depth observations and interviews, and purposive sampling for informant selection. The data was analyzed descriptively to make it easier to read and apply. The results showed that idle land is used with a borrow-and-manage system for short-term agriculture, without permission to build permanent buildings or raise livestock. This land use is very influential on people's lives, being the main source of income for them. The community feels helped by the increase in income from this land.